2020
DOI: 10.1152/japplphysiol.00523.2019
|View full text |Cite
|
Sign up to set email alerts
|

Countdown before voluntary exercise induces muscle vasodilation with baroreflex-mediated decrease in muscle sympathetic nerve activity in humans

Abstract: We examined whether countdown (CD) before voluntary bicycle ergometer exercise induced cerebro‐cardiovascular responses and, if so, whether these responses to CD were altered by postural change from the semi‐recumbent to supine position. Young men (n=14) performed voluntary cycle exercise in the semi‐recumbent position while middle cerebral artery blood flow velocity (CBF; Doppler ultrasonography), heart rate (HR), blood pressure (finger photoplethysmography), oxygen consumption rate (VO2), oxygen saturation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Interestingly, the sympathetic response to preparatory or anticipatory stress appears to be governed by both the stressor type as well as psychological factors. For example, Manabe et al (2020) observed a significantly blunted MSNA response to a countdown prior to exercise initiation, while Brown et al (2013) observed significantly increased MSNA in response to passive viewing of exercise. Further, Holwerda et al (2018) reported significantly elevated peripheral sympathetic outflow in individuals with generalized anxiety disorder during the anticipatory phase prior to mental stress, as well as throughout the stressor itself.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly, the sympathetic response to preparatory or anticipatory stress appears to be governed by both the stressor type as well as psychological factors. For example, Manabe et al (2020) observed a significantly blunted MSNA response to a countdown prior to exercise initiation, while Brown et al (2013) observed significantly increased MSNA in response to passive viewing of exercise. Further, Holwerda et al (2018) reported significantly elevated peripheral sympathetic outflow in individuals with generalized anxiety disorder during the anticipatory phase prior to mental stress, as well as throughout the stressor itself.…”
Section: Discussionmentioning
confidence: 98%
“…Many commonly utilized stress tests are performed with the addition of multiple confounds such as irregular breathing patterns and depth, active talking, muscle movements and other confounds that may impact MSNA recordings and subsequent data interpretation. Recently, anticipatory stress has been shown to significantly impact sympathetic outflow in both healthy individuals (Brown et al., 2013; Manabe et al., 2020) and those with generalized anxiety disorder (Holwerda et al., 2018). Interestingly, the sympathetic response to preparatory or anticipatory stress appears to be governed by both the stressor type as well as psychological factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported similar responses in humans when they intended to start exercise, which were followed by enhanced muscle blood flow and oxygen consumption rate at the onset of exercise (22). Thus, these responses are thought to be one of the feed-forward mechanisms for adjusting cardiovascular functions for starting voluntary exercise smoothly (23).…”
Section: Differences Between Voluntary Movements and Motivated Behaviorsmentioning
confidence: 65%